Problems Of Teaching Speaking Skill And Its Solution Among Students At The Second Public Intermediate School Of Bondowoso For The School Year 2021/2022: مشكلات تدريس مهارة الكلام و حلها عند الطلبة بالمدرسة المتوسطة الحكومية الثانية بوندوصو للسنة الدراسية 2021/2022 - Muhammad Haekal Abdun; Miftah Arifin (Journal of Arabic Language Teaching, 2022)
Speaking is the first productive skill and the primary skill in language teaching. But in fact, teaching speaking skill so far is still under the teacher’s control. It does not allow the students to participate in the teaching activities and exercises actively, so they cannot speak the Arabic language and feel bored teaching it. This research aims to describe the problems faced by language teachers and students at the Second Public Intermediate School of Bondowoso for the school year 2021/2022 in teaching speaking skills, as well as to describe solutions to those problems for teaching Arabic speaking skills. The researcher used qualitative and descriptive research to know the problems of teaching speaking skills and its solution among students at the Second Public Intermediate School of Bondowoso for the school year 2021/2022. The data collection methods in this research are observation, interview, and document. The result of this research is to find the problem for the teacher, which is (1) the teacher’s weak efficiency in speaking skill, (2) the lack of time to teach Arabic, (3) the student’s lack of desire to teach Arabic, (5) the lack of opportunity to practice speaking, ( 6) The lack of an excellent linguistic teaching environment. The problem with the students is (1) Students’ unwillingness to learn Arabic, (2) Different students’ study backgrounds, (3) Some students are unable to pronounce sounds due to problems with them, (4) The teacher’s boring way of teaching speaking skills. As for the solutions to these problems, as told by the teacher, they are: allowing the teacher to improve his efficiency, increasing the share of teaching Arabic, using the preferred method, creating the appropriate environment for teaching Arabic, and encouraging the teacher to promote students’ desire to teach Arabic. الكلام هو المهارة الإنتاجية الأولى، والمهارة الرئيسية في تعليم اللغة. لكن في الواقع أن تعليم مهارة الكلام حتى الآن مازال تحت سيطرة المعلم ولا يتيح الفرصة لدى الطلبة ليشتركو ا بجهد ونشاط في الأنشطة التدريسية والتدريبات حتى أن الدارسين لم يستطيعوا أن يتكلموا باللغة العربية ويشعرون بالملول في تعليم اللغة العربية. هدف هذا البحث لوصف المشكلات التي يوجهها معلموا اللغة و الطلبة بالمدرسة المتوسطة الحكومية الثانية بوندوصو للسنة الدراسية 2021/2022 في تدريس مهارة الكلام, وكذلك لوصف الحلول لتلك المشكلات لتدريس مهارة الكلام للغة العربية. واستخدم الباحث في هذا البحث بحثا کيفيا وصفيا في معرفة مشكلات تدريس مهارة الكلام و حلها عند الطلبة بالمدرسة المتوسطة الحكومية الثانية بوندوصو للسنة الدراسية 2021/2022. وطريقة جمع البيانات في هذا البحث هي طريقة الملاحظة و المقابلة والوثيقة. و نتيجة لهذا البحث إيجاد المشكلة للمعلم و هي (1) ضعفة كفاءة المعلم في مهارة الكلام, (2) ضيق الوقت في تعليم اللغة العربية, (3) قلة الرغبة الطلبة في تعليم اللغة العربية، (5) وقلة الفرصة في ممارسة الكلام ، (6) وعدم بيئة التدريسية اللغوية الجيدة.و المشكلة من التلاميذ، : (۱) عدم رغبة التلاميذ في تعلم اللغة العربية (۲) خلفية دراسية التلاميذ المختلفة (3) بعض التلاميذ غير قادرين على نطق الأصوات لوجود مشکلات عنده (4) طريقة المعلم المملة في تعليم مهارة الكلام. أما الحلول لتلك المشكلات كما أخبرها المعلم و هي: إعطاء الفرصة للمعلم لترقية كفاءته, وزيادة الحصة لتعليم اللغة العربية , واستخدام الطريقة المعجبة, وتكوين البيئة المناسبة لتعليم اللغة العربية, والتشجيع من المعلم لترقية رغبة الطلبة في تعليم اللغة العربية.